Resistance Gene Analogs (RGA) as a tool in fruit tree's breeding - Gutermuth, A.; Pedryc, A. (International Journal of Horticultural Science, 2009)
Breeding for pest and disease resistance comes as a major objective behind the fruit traits. To increase the effectiveness of fruit resistance breeding application of the Marker Assisted Selection ( MAS) is advantageous. For generating molecular markers which enable the following of interesting traits basically two methods are available: targeted marker design based on conservative region of already known Resistance ( R) gene sequences or randomly generated markers. The creation  and the application  of  these homology  based  markers  are the object of this review in  the main  temperate zone  fruit species.